1999
DOI: 10.1074/jbc.274.35.24787
|View full text |Cite
|
Sign up to set email alerts
|

Structural Identification of a Novel Pro-inflammatory Epoxyisoprostane Phospholipid in Mildly Oxidized Low Density Lipoprotein

Abstract: One of the earliest steps in the development of the atherosclerotic lesion is the accumulation of monocyte/ macrophages within the vessel wall. Oxidized lipids present in minimally modified-low density lipoproteins (MM-LDL) contribute to this process by activating endothelial cells to express monocyte-specific adhesion molecules and chemoattractant factors. A major focus of our group has been the isolation and characterization of the biologically active oxidized lipids in MM-LDL. We have previously characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
207
1
10

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 207 publications
(220 citation statements)
references
References 47 publications
2
207
1
10
Order By: Relevance
“…Another possible explanation for these results is that cholesterol accumulation per se is not an inflammatory stimulus or that it is, but that induction of inflammatory molecules occurs at a later time. Support for the former possibility comes from the above-cited study (10), in which activation of SMCs was accomplished by delivery of cholesterol in the form of modified LDL [which contains the inflammatory factors (31,32)], and from studies by Lawn and colleagues (33), which have shown that loading of macrophage cell lines with oxidized LDL leads to increased expression of inflammatory genes and greater responsiveness of these genes to lipopolysaccharide stimulation (34).…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation for these results is that cholesterol accumulation per se is not an inflammatory stimulus or that it is, but that induction of inflammatory molecules occurs at a later time. Support for the former possibility comes from the above-cited study (10), in which activation of SMCs was accomplished by delivery of cholesterol in the form of modified LDL [which contains the inflammatory factors (31,32)], and from studies by Lawn and colleagues (33), which have shown that loading of macrophage cell lines with oxidized LDL leads to increased expression of inflammatory genes and greater responsiveness of these genes to lipopolysaccharide stimulation (34).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, PON1 has also been shown to inhibit LDL oxidation in vitro (24,25). Among the oxidized lipids that PON1 can destroy are 1-palmitoyl-2-(5)oxovaleroyl-sn-glycero-3-phosphorylcholine (POVPC), 1-palmitoyl-2-glutaroyl-sn-glycero-3-phosphorylcholine (PGPC) (34), 2 1-palmitoyl-2-(5,6-epoxyisoprostane E 2 )-sn-glycero-3-phosphorylcholine (PEIPC) (35), 2 and cholesteryl linoleate hydroperoxides (36). PON1 can also destroy hydrogen peroxide (H 2 O 2 ), a major reactive oxygen species produced under oxidative stress during atherogenesis (36), suggesting that it has peroxidase activity as well.…”
Section: Low Density Lipoprotein (Ldl)mentioning
confidence: 99%
“…Paraoxonase (PON1) and platelet-activating factor acetylhydrolase (PAF-AH) are two enzymes complexed with lipoproteins that prevent the accumulation of oxLDL (19 -21). PON1 can inhibit LDL oxidation and destroy various bioactive oxidized phospholipids as well as hydrogen peroxide (22)(23)(24). In the model proposed by Watson et al (20), oxidized phospholipids are first substrate for PON1 in HDL.…”
mentioning
confidence: 99%